Validation and Psychometric Properties of the HEXACO Personality Inventory Observer Report Form in the Polish Language. Issue 6 (24th October 2022) - Misiuro, Tomasz; Gorbaniuk, Oleg; Macheta, Krystian; McNeill, Monika; Kubicka-Jakuczun, Joanna; Kuźmik, Mateusz; Wontor, Paweł; Zajkowska, Marta; Rykowska, Karolina; Świątek, Pamela; Zygnerska, Milena
Abstract: The aim of this study was to verify the structure and psychometric properties of the Polish adaptation of the HEXACO-PI-R observer report form based on a heterogeneous target sample (liked, neutral and disliked peers). The vast majority of research has focused on the validity and reliability of the self-report form. The psychometric properties of the observer report version have been verified in only two languages. Previous Polish lexical studies based on a heterogeneous target sample have shown that the structure differs from a typical six-factor structure from self-rating studies. Since this phenomenon was not observed in English, we decided to verify the psychometric properties of the observer report form in Polish. Additionally, the NEO-FFI and Polish Personality Markers for observer report were used. All HEXACO-PI-R scales achieved satisfactory internal consistency and showed high stability. The results indicated that the structure of the Polish adaptation of the HEXACO-PI-R observer report form could be considered as similar to the theoretical construct, except when the target of the description is neutral for the respondent. This suggests the necessity to verify the structure of the HEXACO-PI-R observer report form based on liked and disliked peers in other languages as well.